Static and Dynamic Buckling of Rectangular Functionally Graded Plates Subjected to Thermal Loading - Czechowski, L.; Kowal-Michalska, K. (Проблемы прочности, 2013)
In the paper, the buckling phenomenon for static and dynamic loading (pulse of finite duration) of functionally graded plates subjected to uniform temperature increment is presented. The work deals with thin rectangular plates with unmovable edges, simply supported or clamped along all edges. The material properties varying smoothly across the thickness are assumed to be temperature-independent. The investigations are conducted for different values of volume fraction index and uniform temperature rise in form of rectangular pulse of finite duration.